WHISTLE BLOWER DAN CROWN WITNESS DALAM PROSES PERADILAN - Moh Rusdyanto Puluhulawa (JURNAL LEGALITAS, 2009)
Explanation of eyewitness is important factor in proting truth in a conference process, this thing is drawn to explains by placing description of eyewitness in first sequence above equipment of other evidence. Remembers position of eyewitness of vital importance in process of court, from criminal court, hence required an institute which able to give guarantee to protection of eyewitness. In Indonesian, term whistle blower unknown to in the law and regulation. Whistle blower can be meant them reporting existence of a crime without involving in the crime, mean doesn\'t follow in crime. Whereas crown witness can mean accused ready to assist investigator to express all crime and unfolds all involving performer. Protection of eyewitness and victim hardly need to be done for the shake of fluency solving af a case. Imaginable f only eyewitness only be aside it go hang after completed executing duty as eyewitness. Feeling is not safe and sneaking would always haunts just for who coincidently becomes eyewitness, because it is not impossible threat in the form of terror even threat will lose soul would come every when.